Therapeutic effect and safety of individualized chemotherapy combined with sequential immunotherapy based on BRCA1 mRNA expression level in unresectable pancreatic cancer - Du, Juan; Zhu, Linxi; Sha, Huizi; Zou, Zhengyun; Shen, Jie; Kong, Weiwei; Zhao, Lianjun; Gu, Qing; Yu, Lixia; Qiu, Yudong; Liu, Baorui (Frontiers in Oncology, 2022)
Aim We aimed to evaluate the efficacy and safety of individualized chemotherapy combined with sequential immunotherapy based on BRCA1 mRNA expression in unresectable pancreatic cancer. Methods The expression of BRCA1 mRNA in tumor tissues of 25 patients with pancreatic cancer was detected in this retrospective study. Patients in the medium and high expression groups were treated with paclitaxel-based chemotherapy: albumin paclitaxel 125mg/m2, gemcitabine 1g/m2, day 1. Patients in the low expression group were treated with oxaliplatin-based chemotherapy: oxaliplatin 85mg/m2, gemcitabine 1g/m2, day 1. Sequential GM-CSF and IL-2 immunotherapy were applied. Patient condition, treatment efficacy and safety were assessed every 4 cycles. Results A total of 25 patients were enrolled in the study. All of them were observed for toxic side effects and 24 of them were evaluated for efficacy. The median overall survival and median progression-free survival were 11.9 months and 6.3 months. The disease control rate was 91.7%, of which 37.5% (9/24) patients achieved partial remission (PR), 54.2% (13/24) patients achieved stable disease (SD) and 8.3% (2/24) patients were assessed as progressive disease(PD). Of the 15 patients with medium or high expression in BRCA1 mRNA, 7 achieved PR and 8 achieved SD. Of the 9 patients with low BRCA1 mRNA expression, 2 achieved PR, 5 achieved SD and 2 had PD. The proportion of eosinophils in the blood of some patients with good therapeutic effects was significantly higher than that before treatment. Hematological and non-hematological toxicity during the treatment were mostly grade 1~2. The two most common grade 3 to 4 adverse events were fever and thrombocytopenia. Conclusion Our results suggest that individualized selection of chemotherapy combined with sequential immunotherapy according to BRCA1 mRNA expression level in unresectable pancreatic cancer could control the disease and have controllable adverse reactions.